Evaluation of the Physiological Workload of Loading Machine Operators During Forestry Work - Melemez, Kenan; Tunay, Metin; Tunay, Metin (Kastamonu Univ, Orman Fak, 2010)
Various loading machines of different type and size are used in loading and stacking of the forest products in the forest depots in Turkey. Heart rate of the loading machine operators is affected by various variables such as machine and the environment. Physiological measurements, including heart rate as well, are a reliable tool in the detection of workload. This study was conducted on 145 operators working in the loading and stacking of forest products in the forest depots in Western Black Sea Region of Turkey. Pulse values of operators during work and rest were measured with Polar pulse timer and belt and physiological workload was tried to be determined. Diastole and systole values, maximum oxygen consumption and maximum heart rate values belonging to operators were put forward and compared with previous studies. Their mean systole value was found to be 79 mmHg, diastole value as 127 mmHg and heart rate as 77 beat/min while resting and as 93 beat/min while working. Mean physiological workload value (HRR%) was calculated as 49% while working with the loading machines and, loading works were found to be classified into medium-heavy work group in workload classification. Old machines and operator seats the dynamic structure of which have been already deformed and which are still used in loading and stacking works should be replaced by the new ones. Important ergonomic factors which are all effective on the physiological workload of the operator should be monitored regularly and, loading works should be carried out in healthier and more productive manner.
Keywords: Forestry; Loader; Operator; Workload; Heart Rate